2012
DOI: 10.1590/s1516-44462012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory factor analysis of the Brazilian version of the Post-Traumatic Stress Disorder Checklist - Civilian Version (PCL-C)

Abstract: Avoidance and numbing seem to be independent dimensions, differently from what is expected according to the DSM-IV. Therefore, new trials should be carried out in other populations, with victims of different kinds of trauma, and including females, to verify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
2
12
0
1
Order By: Relevance
“…Subsequently, using data from a national sample of 1006 male and female veterans, factor analysis supported three factors (re‐experiencing, avoidance, and hyperarousal; Weathers et al, ). While the PCL‐C has been adapted and validated with different ethnic/racial groups (Hem, Hussain, Wentzel‐Larsen, & Heir, ; Passos, Figueira, Mendlowicz, Moraes, & Coutinho, ), an Arabic version of PCL‐C has not been developed.…”
Section: Reliability and Validity Of The Arabic Ptsd Checklist Civilimentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, using data from a national sample of 1006 male and female veterans, factor analysis supported three factors (re‐experiencing, avoidance, and hyperarousal; Weathers et al, ). While the PCL‐C has been adapted and validated with different ethnic/racial groups (Hem, Hussain, Wentzel‐Larsen, & Heir, ; Passos, Figueira, Mendlowicz, Moraes, & Coutinho, ), an Arabic version of PCL‐C has not been developed.…”
Section: Reliability and Validity Of The Arabic Ptsd Checklist Civilimentioning
confidence: 99%
“…While the PCL-C has been adapted and validated with different ethnic/ racial groups (Hem, Hussain, Wentzel-Larsen, & Heir, 2012;Passos, Figueira, Mendlowicz, Moraes, & Coutinho, 2012), an Arabic version of PCL-C has not been developed.…”
Section: Post-traumatic Stress Disorder Symptoms Among Ipv Survivorsmentioning
confidence: 99%
“…The indication of PTSD is confirmed when the person experienced, witnessed, or was confronted by a traumatic event (diagnostic criterion A for PTSD, according to the DSM-IV-TR) and shows a clinically significant symptom of diagnostic criterion B (persistent reliving - measured by the first five items), three symptoms of diagnostic criterion C (avoidant behavior or emotional numbness - items 6 to 12), and two symptoms of diagnostic criterion D (hyperexcitability - items 13 to 17). The instrument considers as a clinically significant symptom a score greater or equal to three, in one of the 17 items ( 11 ) . Thus, this instrument identifies whether a person has or not the indication of PTSD.…”
Section: Methodsmentioning
confidence: 99%
“…2) possible biases in the understanding of certain items, particularly those concerning the phenomenon of hypervigilance (e.g., alterations in arousal and reactivity), as recommended elsewhere. 13,14…”
Section: Translation and Adaptation Proceduresmentioning
confidence: 99%
“…17,19 The original PCL-C was cross-translated and validated in several languages, 21 including Brazilian Portuguese. 6,13,14 Investigations have demonstrated that the original PCL-5 is psychometrically sound. The scale was administered to samples of trauma-exposed college students 22 and US veterans.…”
mentioning
confidence: 99%